Corruption as a national security threat in Iceland - Juan Jose Colorado Valencia 1999- (2024)
Corruption harms societies by fostering inequality, eroding trust in institutions, redirecting resources from essential services, and hindering economic opportunities. This issue extends to different parts of national security, where corrupt activities pose multiple risks to stability and integrity by undermining institutions' capabilities and compromising law enforcement. Thus, national security institutions are increasingly directing their attention towards addressing corruption from local and external sources to safeguard citizens, institutions, and resources for overall societal well-being.This research looks into the contemporary Icelandic context, scrutinising the relationship between corruption and national security threats. Iceland is chosen for analysis due to its distinctive features, including its geopolitical relevance, historical levels of peace, absence of significant local military power, and socio-economic wealth, making it a compelling subject for investigating this relationship. Given the limited available data on how corruption undermines Icelandic national security, in-depth interviews with experts from diverse fields were conducted to comprehend the multifaceted nature of this issue. Through a qualitative risk assessment, the gathered data identified vulnerabilities, risks, levels of concern, and recommendations for further improvement. Acknowledging the correlation between corruption and national security threats, it is argued that supporting the efforts of integrating anti-corruption measures into national security strategies is the most effective approach, fostering awareness and allocating resources. While the effectiveness of this approach is still under evaluation, preliminary indications suggest promising outcomes.